ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIS DAN SELF EFFICACY SISWA MAN - Ita Nur Indahsari; Jayanna Clarita Situmorang; Risma Amelia (Journal on Education, 2019)
This study aims to determine students' mathematical problem solving abilities and self efficacy. Data retrieval was carried out in the Public MA in the city of Cimahi with a sample of research, namely the XI MIA 3 class consisting of 34 students. The method used is descriptive analysis by providing instruments and questionnaires. The results of the study obtained results: (1) achievement of mathematical problem solving abilities on the given problem; (2) errors when working on the problem; (2) students' self efficacy from the questionnaire according to their indices. It can be seen that students 'mathematical problem solving abilities in high categories and students' self efficacy are good